Effects of Reels and short videos on human mind and Academic Life - Vishal Mugdal; Kinjal Doshi (International Journal of Behavioral Sciences, 2026)
The rapid rise of short-form video platforms such as Instagram Reels, TikTok, and YouTube Shorts has fundamentally reshaped the way people consume information and entertainment. While these applications offer quick engagement and social connection, their excessive use has raised serious concerns about their psychological and academic impacts. This research investigates the relationship between short-form video addiction, mindfulness, academic anxiety, and academic engagement among university students. Drawing upon the theoretical framework of cognitive-behavioral addiction and mindfulness theory, this study examines how addiction to short- form videos influences learners’ emotional well-being and academic functioning.A cross-sectional quantitative design was employed with data collected from 1,879 undergraduate students through validated scales: the Short-Form Video App Addiction Scale, the Mindful Attention Awareness Scale (MAAS), the Academic Anxiety Sub-questionnaire, and the Academic Engagement Scale. Data were analyzed using SPSS 20.0 and AMOS 24.0 for reliability, validity, and structural equation modeling (SEM). Findings reveal that short-form video addictionThe digital era has ushered in a revolution in how people consume and share information. Among the most influential developments in recent years is the rise of short-form video platforms such as Instagram Reels, TikTok, and YouTube Shorts. These platforms deliver high-intensity, visually stimulating content in a matter of seconds, appealing particularly to younger audiences who seek instant gratification and continuous entertainment. While short videos provide a creative outlet for expression, social connection, and rapid knowledgeThe rapid rise of short-form video platforms such as Instagram Reels, TikTok, and YouTube Shorts has fundamentally reshaped the way people consume information and entertainment. While these applications offer quick engagement and social connection, their excessive use has raised serious concerns about their psychological and academic impacts. This research investigates the relationship between short-form video addiction, mindfulness, academic anxiety, and academic engagement among university students. Drawing upon the theoretical framework of cognitive-behavioral addiction and mindfulness theory, this study examines how addiction to short- form videos influences learners’ emotional well-being and academic functioning.A cross-sectional quantitative design was employed with data collected from 1,879 undergraduate students through validated scales: the Short-Form Video App Addiction Scale, the Mindful Attention Awareness Scale (MAAS), the Academic Anxiety Sub-questionnaire, and the Academic Engagement Scale. Data were analyzed using SPSS 20.0 and AMOS 24.0 for reliability, validity, and structural equation modeling (SEM). Findings reveal that short-form video addictionThe digital era has ushered in a revolution in how people consume and share information. Among the most influential developments in recent years is the rise of short-form video platforms such as Instagram Reels, TikTok, and YouTube Shorts. These platforms deliver high-intensity, visually stimulating content in a matter of seconds, appealing particularly to younger audiences who seek instant gratification and continuous entertainment. While short videos provide a creative outlet for expression, social connection, and rapid knowledgesignificantly increases academic anxiety while reducing academic engagement. Mindfulness serves as a key mediating factor, mitigating the negative effects of excessive short-video consumption on students’ emotional regulation and learning motivation. The study highlights the importance of integrating mindfulness-based interventions within academic environments to reduce digital dependence and enhance students’ concentration and resilience.This research contributes to the growing body of literature on digital media psychology by emphasizing how compulsive engagement with reels and short videos affects mental health and learning outcomes. The results underscore the need for balanced digital habits, self-awareness training, and institutional policies promoting healthy media consumption patterns.
Keywords: Academic Anxiety; Academic Engagement; Addiction; Digital Psychology; Reels; Short-form Videos; mindfulness; student well-being